2017
DOI: 10.1007/s10973-017-6233-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of hydration products of fly ash–slag pastes

Abstract: The paper presents the results of the research identifying the hydration products present in hardened fly ash-slag pastes considered as alternative non-clinker binder. Thermal analysis (TG/DTG), infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) were used as complementary methods. The pastes contained the binder made of two components: fly ash from circular fluidized bed combustion of brown coal and ground granulated blast furnace slag. The components were mixed accordingly to five formulas di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…In the case of PF, the presence of crystalline aluminosilicate phase, probably type of muscovite, is registered. X-ray diffraction patterns confirm general differences in composition of fly ashes coming from conventional and fluidized combustion, and the results agree with literature data, e.g., [42,51,52,54,55].…”
Section: Fly Ashessupporting
confidence: 88%
See 1 more Smart Citation
“…In the case of PF, the presence of crystalline aluminosilicate phase, probably type of muscovite, is registered. X-ray diffraction patterns confirm general differences in composition of fly ashes coming from conventional and fluidized combustion, and the results agree with literature data, e.g., [42,51,52,54,55].…”
Section: Fly Ashessupporting
confidence: 88%
“…Recently, we studied mixtures composed of fluidized fly ash and blast furnace slag as nonclinker binder in which fly ash was considered as activator for slag. Results of investigation of hydration products arising in such systems were presented in [51]. The results are promising and encourage further research of, e.g., activated systems containing a very high amount of fluidized fly ash and a small amount of cement.…”
Section: Introductionmentioning
confidence: 85%
“…Overall, SCA met the requirements for structural concrete [117]. Kledynski et al [118] identified the hydration products present in hardened SCA pastes. Their results revealed the progression of the hydration process over time and the formation of products similar to those present in hardened cement pastes.…”
Section: Mixtures Of Industrial Waste Materialsmentioning
confidence: 95%
“…Depending on the type of aluminosilicate source material as well as conditions of reaction (such as concentration of alkali and temperature), this product may be zeolitic or amorphous [4-6, 8, 9]. There are also research reports concerning utilisation of fly ash from fluidised combustion of coal as activator for slag component in nonclinker mixture [28,29].…”
Section: Introductionmentioning
confidence: 99%